The administration of Hugh of Wells, Bishop of Lincoln 1209-1235 - Smith, David Michael (1970)
In the latter half of the twelfth century and at the beginning of the thirteenth, the machinery and methods of Episcopal government in several English bishoprics were improved and transformed by the actions of certain competent and energetic prelates. The following study aims to record and assess the achievements of one such bishop - Hugh of Wells, for twenty-six years occupant of the see of Lincoln. Hugh's experience of Hubert Walter's reforms in the royal chancery and his implementation of this knowledge to diocesan government after his elevation to the bishopric of Lincoln culminated in a pontificate marked by transition and innovation in the sphere of administrative procedure - notably, the registration of certain categories of diocesan business upon rolls. An examination of these enrolments in conjunction with the four hundred surviving acta of the bishop has allowed a more detailed insight into many aspects of routine ecclesiastical government than at first appeared possible. Yet, even the resultant study is by no means an exhaustive record of the conduct of diocesan affairs under this very efficient but otherwise unremarkable bishop. The central bureaucracy of the diocese, its composition and recruitment, the division of duties between the various administrative officials and the bishop's relations with the regular and secular clergy under his control have all merited close attention but in the event it has proved impossible to include in this thesis a survey of the administration of the temporalities of the see during Hugh's episcopate even though ample source material is available for such a project.